Trysor y Môr-Ladron - Jones, T. Llew (Gomer Press, 1989)
An exciting novel for children about Sir Henry Morgan, the famous pirate, as he looks for treasure. Intro – Teitl – Hawlfraint – Cynnwys – 1 – 2 – 3 – 4 – 5 – 6 – 7 – 8 – 9 – 10 – 11 – 12 – 13 – 14 – 15.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books